Synthesis, Characterizations, Anti-Diabetic and Molecular Modeling Approaches of Hybrid Indole-Oxadiazole Linked Thiazolidinone Derivatives - Shoaib Khan; Tayyiaba Iqbal; Rafaqat Hussain; Yousaf Khan; Zanib Fiaz; Fazal Rahim; Hany W. Darwish (Pharmaceuticals)
Objective: To synthesize hybrid compounds of indole and oxadiazole in search of highly effective anti-diabetic therapeutic agent. Methods: With the goal of advancing diabetes research, our group designed and synthesized a library of 15 compounds based on indole-derived oxadiazole bearing varied substituted thiazolidinone via a multistep synthetic route. 13C-NMR, 1H-NMR and HREI-MS were applied for the characterization of all the synthesized compounds. Their biological inhibitory activity against diabetic enzymes, i.e., α-amylase and α-glucosidase was also determined. Results: Compound 7, 9 and 15 exhibited excellent inhibition against α-amylase and α-glucosidase than the standard acarbose (IC50 = 8.50 ± 0.10 µM for α-amylase and 9.30 ± 0.30 µM for α-glucosidase. To ensure the inhibitory actions of these potent analogs in molecular docking, an in silico approach was used. To determine the drug likeness of the reported analogs, an ADMET investigation was also carried out to explore the nature of the designed compounds if used as a drug. Conclusion: Fluoro-substituted analog 15 has stronger inhibition profile against both enzymes. All the potent compounds can be used as effective anti-diabetic therapeutic agents in future.